The use of technology in Prince Edward Island (Canada) high schools: Perceptions of school leaders. (November 2015) - Preston, Jane P; Moffatt, Lyndsay; Wiebe, Sean; McAuley, Alexander; Campbell, Barbara; Gabriel, Martha
The purpose of this paper is to document the perceptions of school leaders regarding the technological use, skills, and attitudes of high school teachers. Using a qualitative research approach, 11 educational leaders from Prince Edward Island (Canada) were individually interviewed. Participants represented the Department of Education, principals, vice-principals, and department heads. Analyzed through the concept of e-leadership, the findings indicated that participants used a growing array of technological tools and activities including Smartboards, flipped classrooms, Prezi, educational apps, YouTube, and teacher blogs. Participants identified lack of time as a possible reason why some teachers were not incorporating technology into student learning. Findings highlight the need for provincial and school district authorities to promote policies aimed at promoting e-leadership among teachers. We insert an appendix to provide descriptions of the technological terms included within the paper.